Promoting health and academic success the whole school, whole community, whole child approach - Birch, David A.; Videto, Donna M. (Human Kinetics, 2015)
This book provides direction for education and school health professionals interested in promoting student health and is valuable for individuals and groups interested in advocating for WSCC and for those engaged in the planning, implementation and evaluation of this new approach.